Síntese de 1h-1,2,3-triazóis trialoacetil substituídos análogos estruturais da rufinamida - Moraes, Maiara Correa de (2013)
The present dissertation describes a chemical methodology for the synthesis of three series containing fourteen new molecules of trifluoro(chloro)methyl substituted 1H-1,2,3-triazoles, which are structural analogues to the antiepileptic drug Rufinamide. The protocol used consisted in reactions of 1,3-dipolar cycloaddition of 2,6-difluorobenzyl azide and 4-alkoxy-4-alkyl(aryl/heteroaryl)-1,1,1-trifluoro(chloro)-3-alken-2-ones, where the 4-substituents are H, Me, Ph, 4-OMeC6H4, 4-NO2C6H4,4-FC6H4,2-Thienyle 4,4 -Biphenyl. The optimized reactios were carried-out in absense of solvente, in reaction times of 48 to 96 hours at 100-150°C and in yields of 30-75%. The reactions employing the 4-alkoxy-4-aryl(heteroaryl)-1,1,1-trifluoro-3-alken-2-ones 1and 2,6-difluorobenzyl azidedemonstrated a 4-substituent dependency of the enones precursors (above mentioned) and conducted to the formation of isomeric mixtures of 4-trifluoroacetyl substituted and/or 5-trifluoromethyl substituted triazoles in varying proportions, which were separated and purified by chromatographic columns. On the other hand, the reactions employing the 4-alkoxy-4-alkyl(aryl/heteroaryl)-1,1,1-trichloro-3-alken-2-ones and the same 2,6-difluorobenzyl azide produced exclusively a series of 4- trichloroacetyl substituted triazoles without the detection of the respective 5-trichloromethyl substituted regioisomer. The synthesized triazoles were characterized by 1H, 13C, uni- and two-dimensional NMR Spectroscopy techniques as HMQC, gas chromatography coupled to mass spectrometry (GC-MS), mono-crystal X-ray diffraction, high resolution mass spectrometry (HRMS) and their purity determined by CHN Elemental Analysis.